2009
DOI: 10.3748/wjg.15.753
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus mutations potentially conferring adefovir/tenofovir resistance in treatment-naive patients

Abstract: Anti-hepatitis B virus (HBV) therapy leads to the emergence of mutant viral strains during the treatment of chronic hepatitis B with nucleos(t)ides analogues. The existence of HBV variants with primary antiviral resistance may be important for treatment choice. We studied two patients with chronic HBV infection by sequencing the HBV polymerase gene. They had adefovir-and tenofovir-related mutations in the viral polymerase, although they had never been treated. These mutations were rtV214A/rtN238T in one patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Meanwhile, the results also suggested that NA treatment is the major selecting factor of primary drug-resistant mutations and that NA treatment promotes putative NAr mutations (Li et al, 2012). Moreover, several previous studies showed that primary NAr mutations occur in patients with no history of NA treatment (Han et al, 2009;Kobashi et al, 2009;Pastor et al, 2009). Recently, another paper also reported that HBV resistance mutations were identified in 5 % of treatment-naïve patients by using INNO-LiPA (Fujirebio) line probe analysis (Mirandola et al, 2011).…”
mentioning
confidence: 99%
“…Meanwhile, the results also suggested that NA treatment is the major selecting factor of primary drug-resistant mutations and that NA treatment promotes putative NAr mutations (Li et al, 2012). Moreover, several previous studies showed that primary NAr mutations occur in patients with no history of NA treatment (Han et al, 2009;Kobashi et al, 2009;Pastor et al, 2009). Recently, another paper also reported that HBV resistance mutations were identified in 5 % of treatment-naïve patients by using INNO-LiPA (Fujirebio) line probe analysis (Mirandola et al, 2011).…”
mentioning
confidence: 99%
“…Nonetheless, antiviral therapy with these drugs is often ineffective because of the emergence of antiviral-drug resistance mutations, located in the HBV reverse transcriptase (RT) gene during long-term treatment (1). Therefore, antiviral-drug resistance mutations have even been reported in HBV isolated from treatment-naïve patients (2,3) HBV RT mutations are classified into 4 categories: primary drug resistance mutations, secondary, or compensatory mutations, putative NA resistance (NAr) mutations, and pretreatment mutations (4). Primary drug resistance mutations are directly responsible for NA resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports showing the existence of antiviral resistance strains in treatment-naïve hepatitis B individuals alert the need for baseline monitoring of antiviral resistance mutants [19][20][21] . Hence in the present study we attempted to identify and analyze the HBVrt amino acid substitutions capable of conferring resistance to antivirals in treatment-naïve HBV-infected individuals from the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%